2021
DOI: 10.1021/acs.jproteome.1c00224
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Systemic Recovery and Metabolic Phenoreversion in Post-Acute-Phase Nonhospitalized COVID-19 Patients: Implications for Assessment of Post-Acute COVID-19 Syndrome

Abstract: We present a multivariate metabotyping approach to assess the functional recovery of nonhospitalized COVID-19 patients and the possible biochemical sequelae of “Post-Acute COVID-19 Syndrome”, colloquially known as long-COVID. Blood samples were taken from patients ca. 3 months after acute COVID-19 infection with further assessment of symptoms at 6 months. Some 57% of the patients had one or more persistent symptoms including respiratory-related symptoms like cough, dyspnea, and rhinorrhea or other nonrespirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
140
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 94 publications
11
140
0
Order By: Relevance
“…An individual can only be thought of as "fully recovered "when their biochemical profiles are substantially normalized with respect to the earlier systemic perturbations seen in the acute phase. This process of normalization is effectively the opposite of disease phenoconversion (Kimhofer et al 2020) and we refer to this process as Phenoreversion and this can be measured metabolically (Holmes et al 2021). Phenoreversion appears to be highly variable between individuals ranging between complete or full recovery, to partial recovery or no recovery, with residual immunologically driven long-term biochemical effects (Holmes et al 2021).…”
Section: Systemic Post-acute Covid-19 Syndrome Phenoreversion and Patient Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…An individual can only be thought of as "fully recovered "when their biochemical profiles are substantially normalized with respect to the earlier systemic perturbations seen in the acute phase. This process of normalization is effectively the opposite of disease phenoconversion (Kimhofer et al 2020) and we refer to this process as Phenoreversion and this can be measured metabolically (Holmes et al 2021). Phenoreversion appears to be highly variable between individuals ranging between complete or full recovery, to partial recovery or no recovery, with residual immunologically driven long-term biochemical effects (Holmes et al 2021).…”
Section: Systemic Post-acute Covid-19 Syndrome Phenoreversion and Patient Recoverymentioning
confidence: 99%
“…This process of normalization is effectively the opposite of disease phenoconversion (Kimhofer et al 2020) and we refer to this process as Phenoreversion and this can be measured metabolically (Holmes et al 2021). Phenoreversion appears to be highly variable between individuals ranging between complete or full recovery, to partial recovery or no recovery, with residual immunologically driven long-term biochemical effects (Holmes et al 2021). It was also notable that the non-hospitalised mildly affected patients at 3-month follow-up also included some new phenotypic changes not observed in the controls or the acute phase patients.…”
Section: Systemic Post-acute Covid-19 Syndrome Phenoreversion and Patient Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…289 Indeed, it has been shown that the kynurenine/tryptophan ratio remained elevated in some postacute Covid 19 patients and the question was raised if this may be a marker for the development of PASC. 305 Summary: plausibly, the "metabolic trap" hypothesis may support a central role of the astroglial compartment in the pathophysiology of ME/CFS.…”
Section: The "Metabolic Trap" Hypothesismentioning
confidence: 98%
“…425  There may be microbiome changes in some PASC cases as supported by the observation of increased levels of 3-indole acetic acid which implies a microbiome functionality shift. 305  It seems that the activation of the innate immune system may play a central role in PASC. For one, elevated IL-1beta seems to be a consistent signal in studies of PASC.…”
Section: Covid-19 To the Rescuementioning
confidence: 99%